Edukasi Dan Pelatihan Teknik Pernapasan Relaksasi Bagi Ibu Hamil Sebagai Upaya Komplementer Dalam Mengurangi Nyeri Persalinan Di STIKes Mitra Sejati - Adelina Fitri Tanjung; Eka Ristin Taringan; Lissa Soffia; Yulia A Manullang (STIKES Columbia Asia Medan, 2026)
Pregnancy and childbirth are physiological processes often accompanied by pain resulting from uterine contractions and fetal descent through the birth canal. Relaxation breathing technique is one complementary approach used to reduce labor pain. This community service activity aimed to improve the knowledge and skills of third-trimester pregnant women at STIKes Mitra Sejati regarding relaxation breathing techniques as a nonpharmacological method for reducing labor pain. The methods applied included interactive lectures, question-and-answer sessions, demonstration, and hands-on practice, evaluated through a pretest and posttest within a single activity cycle. The results showed an improvement in participants' knowledge, with the